Force of words : the logic of terrorist threats - Brown, Joseph M. (Columbia studies in terrorism and irregular warfare., 2020)
"Terrorist groups achieve notoriety through acts of violence, but often threats of potential or upcoming violence are just as effective. Threats disrupt economies and ensnare security forces; they frighten civilians and encourage supporters; and they build credibility and force opponents to make concessions. Force of Words is a groundbreaking examination of the role of threats in terrorist strategies that explains the broader purpose and meaning of terrorist propaganda. Joseph M. Brown explains how terrorist groups tailor their threats so that the desired political message is sent. He scrutinizes why terrorists issue warnings of imminent attacks and pledges of violence, and examines their use of hoaxes and bluffing. Drawing on rich interview data, quantitative evidence, and case studies of the Irish Republican Army, ETA, the Tamil Tigers, Shining Path, the Túpac Amaru Revolutionary Movement, Boko Haram, the Afghan Taliban, and ISIL, Brown explores the ways that terrorists use language. He demonstrates that when terrorists rely on civilian support, fight democracies, seek social control, or demand negotiations, their threats should be taken seriously. By identifying the conditions that incentivize particular types of threats, Brown offers practical guidance for interpreting and assessing terrorists' statements. A bold and rigorous consideration of terrorism's tactical and strategic logic, Force of Words sheds new light on the symbolic, psychological dimension that makes this form of political violence distinctive"--